Parenting in protracted refugee situations - Khraisha, Qusai (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2025)
Millions of parents must raise their children in displacement. Though our knowledge of these experiences continues to grow, it is currently undermined by dated approaches relating to how and where ‘refugee parenting’ should be studied. As outlined in Chapter 1, these limited approaches manifest in three significant ways: contextually, the research disproportionately focuses on the unusual 1% of refugees who reach resettlement destinations, systematically overlooking the vast majority living in protracted refugee situations. Conceptually, frameworks to study parenting typically apply individualistic perspectives, viewing parenting solely as ‘mothering’ and disregarding the relational networks central to many refugee families. Methodologically, the literature heavily relies on costly and labour-intensive approaches for data synthesis, while tools designed to gather empirical data on ‘refugee parenting’ are either highly prone to social desirability bias or lack rigorous and appropriate validation, having been mostly developed and established within contexts foreign to most displaced populations. I take a threefold approach to addressing these gaps: (i) find and redirect attention to research conducted on the 78% of displaced people in protracted refugee situations, (ii) expand conceptual frameworks to include ‘refugee coparenting,’ and (iii) optimise current methodological approaches to data collection and synthesis. In Chapter 2, I conduct the first systematic review to explicitly focus on parenting and mental health in protracted refugee situations, analysing nearly 20,000 documents spanning over 70 countries. Studies reviewed indicate that stressors characteristic to populations in protracted refugee situations, such as movement restrictions and employment limitations, have both universal and culturally specific impacts on parents’ mental health, which in turn, shape ‘refugee parenting’ behaviours. In addition to highlighting several methodological weaknesses, including the limited use of live or video observational data, some evidence suggested that the impacts of protracted refugee situations were mediated by the ‘family system’ in such a way that the response of other family members, including the child, played a role in the parenting behaviour of refugee parents. What follows in Chapter 3 is the first dyadic qualitative investigation of ‘refugee coparenting,’ where parenting is approached and enacted collaboratively among refugee mothers and fathers in a protracted refugee situation. I identify four approaches characterising how refugee couples navigated coparenting interactions: negotiation, mirroring, anchoring, and transformation. Specifically, Syrian couples negotiated how to balance responsibilities, sought verbal and non-verbal emotions and behaviours that reflected calm and respect, prioritised family togetherness over education or resettlement opportunities, and adopted gentler parenting approaches to transform intergenerational experiences. These findings illuminate key relational aspects underpinning the ‘family system’ in the context of protracted refugee situations. Chapter 4 builds on findings from Chapters 2-3, particularly the lack of live and video observational studies in the field as confirmed by the systematic review and the emphasis on non-verbal ‘refugee parenting’ behaviours, as highlighted in the theme of mirroring by the qualitative study. I develop and validate the Observational Behavioural System Evaluating Sensitivity and Synchrony (OBSESS) in the first longitudinal study that uses behavioural observation with displaced families. I demonstrate OBSESS’s reliability across multiple tests and time points, and how it captures behaviours that parental self-reports did not fully reflect. Here I also discuss the issue of expensive proprietary observation systems as a significant reason for the limited use of video data in the ‘refugee parenting’ literature, which is why OBSESS is made free and open-access. I continue addressing the issue of cost in Chapter 5, focusing this time on efficient approaches to synthesis of ‘refugee parenting’ research—which is done to address the methodological challenge of managing voluminous and heterogeneous literature that characterised my work in Chapter 2. To this end, Chapter 5 showcases the first evaluation of Generative Pre-trained Transformer 4 (GPT-4), the biggest Large Language Model at the time, against human performance in conducting systematic reviews––based on the review material from the start of the thesis. Findings indicate that while substantial caution should be exercised if LLMs are being used to conduct systematic reviews, they also offer preliminary evidence that, for certain review tasks delivered under specific conditions, LLMs can rival human performance. Chapter 6 discusses the implications of having more inclusive research tools and the added value of analysing the relational aspect of parenting in protracted refugee situations. Taken together, my thesis advances the field in multiple ways: by systematically and comprehensively identifying literature associated with the most prevalent displacement context; by applying a more expansive relational conceptual framework grounded in the everyday experiences of refugee families; and by enabling more rigorous, efficient, and inclusive research approaches.
APPROVED